2020
DOI: 10.1002/cite.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Steel Mill Gas‐Based Methanol Production within the Carbon2Chem® Project

Abstract: Within the Carbon2Chem® project, new processes have been developed to valorize steel mill gases by producing methanol. This article compares the global warming impact of integrated steel and methanol production to the stand‐alone production of steel and methanol. In order to generate mass and energy balances of the cross‐industrial network, several simulation approaches were conducted, and two power sources investigated. In the case of a power mix in 2030, the conventional production of steel and methanol is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In Duisburg, the steel mill gases are first burned to produce steam, which is then converted to electricity with an efficiency of 37 %. A simulation of the steel mill-based methanol production and the corresponding LCA showed that the power plant is still operated within the cross-industry Carbon2Chem network if all steel mill gases are used as feedstock for the methanol plant [11]. In an integrated Carbon2Chem plant consisting of at least one power plant and an SOEC the required steam (150°C, 0.7 kWh Nm - based on an estimate of the steam's energy content.…”
Section: Comparison Of Water Electrolysis Technologies 31 Specific Ementioning
confidence: 99%
See 1 more Smart Citation
“…In Duisburg, the steel mill gases are first burned to produce steam, which is then converted to electricity with an efficiency of 37 %. A simulation of the steel mill-based methanol production and the corresponding LCA showed that the power plant is still operated within the cross-industry Carbon2Chem network if all steel mill gases are used as feedstock for the methanol plant [11]. In an integrated Carbon2Chem plant consisting of at least one power plant and an SOEC the required steam (150°C, 0.7 kWh Nm - based on an estimate of the steam's energy content.…”
Section: Comparison Of Water Electrolysis Technologies 31 Specific Ementioning
confidence: 99%
“…Therefore, the carbon footprint of the hydrogen production is an important ecological parameter for the chemical downstream process. The life cycle assessment (LCA) of the steel mill gas-based production within Carbon2Chem shows that the water electrolysis has a significant impact on the overall CO 2 emissions of the Carbon2Chem network and that an electricity mix with a carbon intensity of less than 0.2 t CO 2 e MWh -1 is required to reduce CO 2 emissions [11]. In the process quoted here, the carbon footprint of the hydrogen production equates to approx.…”
Section: Introductionmentioning
confidence: 99%
“…The concepts investigated by dynamic simulation mainly differ in synthesized product, used type and quantity of steel mill gases, and used technical components, e.g., gas conditioning units and gas buffers. A simulation case is defined from these elements and provides an answer to the mass and energy flows in the process diagram, which can then be used to draw conclusions on economic and ecologic efficiency (see Thonemann et al [12][13][14]). Here, four process concepts C1 to C4 for the production of methanol and urea are developed for simulation.…”
Section: Process Conceptsmentioning
confidence: 99%
“…From the power scenarios with a variable CF, it can be deduced that MeOH production is only ecologically favored below a CF of 162 t CO2 GWh -1 . It should be mentioned that only the operation of the overall network is considered and not, as with other methods like in the work from Thonemann and Maga [17], the comparison between the ecology of stand-alone and coupled production.…”
Section: Casementioning
confidence: 99%
“…Thonemann et al [15] showed the impact of the power grid mix in a life cycle assessment for methanol production with the integration of the power forecasting tool named energy system development plan (ESDP) from [16]. Thonemann and Maga [17] ecologically compared stand-alone and coupled steel and methanol production. Stießel et al [18] identified and evaluated promising concepts and key factors for carbon capture and utilization (CCU) in the steel and chemical industry with respect to future product and energy markets in 2030.…”
Section: Introductionmentioning
confidence: 99%